2005
DOI: 10.1093/jat/29.8.838
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Intoxication Following the Ingestion of 5-Methoxy-N,N-Dimethyltryptamine in an Ayahuasca Preparation*

Abstract: A case of a 25-year-old white male who was found dead the morning after consuming herbal extracts containing beta-carbolines and hallucinogenic tryptamines is presented. No anatomic cause of death was found at autopsy. Toxicologic analysis of the heart blood identified N,N-dimethyltryptamine (0.02 mg/L), 5-methoxy-N,N-dimethyltryptamine (1.88 mg/L), tetrahydroharmine (0.38 mg/L), harmaline (0.07 mg/L), and harmine (0.17 mg/L). All substances were extracted by a single-step n-butyl chloride extraction following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 14 publications
0
85
0
4
Order By: Relevance
“…Although the trafficking, distribution, and abuse of 5-MeO-DMT are likely underreported because it was not a controlled drug before 2011, the System to Retrieve Information from Drug Evidence revealed 23 cases involving 35 drug exhibits identified as 5-MeO-DMT from 1999 to 2009, and the National Forensic Laboratory Information System documented 27 state and local drug cases involving 32 drug exhibits identified as 5- MeO-DMT from 2004(Drug Enforcement Administration, 2010. With the epidemic of abuse, indolealkylamine intoxications have been frequently reported in hospitals in recent years, including several deaths associated with the abuse of 5-MeO-DMT and 5-methoxy-N,Ndiisopropyltryptamine (Brush et al, 2004;Sklerov et al, 2005;Tanaka et al, 2006;Hill and Thomas, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the trafficking, distribution, and abuse of 5-MeO-DMT are likely underreported because it was not a controlled drug before 2011, the System to Retrieve Information from Drug Evidence revealed 23 cases involving 35 drug exhibits identified as 5-MeO-DMT from 1999 to 2009, and the National Forensic Laboratory Information System documented 27 state and local drug cases involving 32 drug exhibits identified as 5- MeO-DMT from 2004(Drug Enforcement Administration, 2010. With the epidemic of abuse, indolealkylamine intoxications have been frequently reported in hospitals in recent years, including several deaths associated with the abuse of 5-MeO-DMT and 5-methoxy-N,Ndiisopropyltryptamine (Brush et al, 2004;Sklerov et al, 2005;Tanaka et al, 2006;Hill and Thomas, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 5-MeO-DMT is often coabused with MAO-A inhibitors (MAOIs), such as harmaline, to enhance its hallucinogenic effects (Ott, 1999(Ott, , 2001Brush et al, 2004;Sklerov et al, 2005). Coabuse of harmaline and 5-MeO-DMT is reasoned to cause complex drug-drug interactions (DDIs).…”
Section: Introductionmentioning
confidence: 99%
“…Before that, 5-MeO-DMT was available on the Internet as a natural product or synthetic compound. 5-MeO-DMT intoxications were also documented (Brush et al, 2004;Sklerov et al, 2005), and the symptoms included extremely high body temperature and heart rate, as well as combative hallucinating without vital signs. Particular attention (Sklerov et al, 2005;Callaway et al, 2006) was drawn to a fatal case in which a strikingly high concentration of 5-MeO-DMT was found in the decedent's heart blood.…”
mentioning
confidence: 99%
“…Its woody vines are an ingredient of the popular psychoactive drink, Ayahuasca [22], which is used for prophecy and as a sacrament in South America. Main active substances (MAOIs) of B .…”
Section: Illegal Plant Species Descriptionmentioning
confidence: 99%
“…Use of DMT causes strong visual effects, euphoria and hallucinations [24]. After ingestion of ayahuasca also effects such as: nausea, changes in visual and auditory perception, psychological introspection, stimulation and blood pressure increase were reported [22]. Serrano-Dueñas et al [25] reported significant improvement in motor functions of the patients in trial of B .…”
Section: Illegal Plant Species Descriptionmentioning
confidence: 99%